THE SOCIAL IMPORTANCE OF THE BENEFITS OF A GREEN ECONOMY - Anton Čiernik; Ingrid Šabíková; Igor Turuk (Polityki Europejskie, Finanse i Marketing)
The Slovak Republic, as a Member State of the European Union, is committed to meet the strategic objective, which is to “significantly increase the competitiveness and performance of the regions of the Slovak economy and employment, while respecting sustainable development”. Today's status of environmental pollution is a global problem, especially in the field of air protection, minimization of adverse effects of climate changes, the promotion of renewable energy sources, water conservation and the rational use and protection of land. Sustainable development represents the evolution of human society while preserving the environment for future generations. The article1 is focused on the strategic priorities with the aim of achieving economic growth in conjunction with the ecology and the quantification of indirect effects. The article describes the multi-criteria decisional analysis, which takes into account the indirect effects in the form of environmental aspects. At the end of the article the benefits of research are articulated.